Adsorption and electro-oxidation of N-alkyl and N,N’-dialkyl thioureas on gold electrodes in acid solutions. A combined FTIRRAS and voltammetry study - Bolzán, Agustín Eduardo (2008)
The adsorption and electro-oxidation of N-alkyl and N,N’-dialkyl thioureas on polycrystalline gold in aqueous acid solutions is studied by Fourier-transformed infrared reflection absorption spectroscopy (FTIRRAS) and voltammetry. The potential ranges for different electrochemical processes, including electrodissolution of gold and electro-oxidation of thioureas, are determined by cyclic voltammetry. The gradual depletion of thioureas and the progressive formation of products from adsorbed and soluble species in the thin solution layer in contact with the electrode are followed through changes in band intensity of infrared (IR) spectra. Adsorbates of thioureas are formed at 0.05 Vand remain on the surface up to E=1.2 V, a potential at which their electro-oxidation takes place. Irrespective of the type of thiourea, the first electro-oxidation process from soluble thioureas starts at ca. 0.45 V with the formation of their respective disulphide. This process is preceded by the electrodissolution of gold via the formation of gold–thiourea soluble complex species. From ca. 1.2 V upwards the second electro-oxidation process results in the formation of carbon dioxide, sulphate ions and C≡N-containing species. The latter are produced only from N-alkyl thioureas, in which the presence of free amine groups makes the formation of a C≡N bond possible, as a previous stage to the production of carbon dioxide and sulphate ions as final products. From the correlation between voltammetric and spectroscopic data a general reaction pathway for the adsorption of thioureas and their electro-oxidation on gold is advanced.